The Enactive Nature of the Relationship between Criticism and Aesthetics: From Practice to Theory to Pedagogy - Ivan Magrin-Chagnolleau (Creative Arts in Education and Therapy)
This article delves into the intricate relationship between criticism and aesthetics, emphasizing its enactive nature. It explores how this relationship informs pedagogy and has culminated in the creation of an innovative undergraduate aesthetics course centered around the practice of writing critiques. Moreover, it illustrates the dynamic process through which practice gives rise to theory, subsequently influencing pedagogical approaches, and, intriguingly, circling back to practice. To elucidate this flow of ideas across the realms of practice, theory, and pedagogy, we introduce several key concepts. These include the paradigm of creation research, also known as practice as research, which forms the foundation for much of our exploration. Additionally, we delve into the paradigm of enaction, inspired by the work of Francisco Varela in the cognitive sciences, to shed light on the cognitive processes underpinning our study. This article is the culmination of nearly a decade of interdisciplinary research that traverses the domains of creation research, enaction, phenomenology, criticism, aesthetics, and pedagogy. Throughout this journey, we have sought to unravel the intricate connections between criticism and aesthetics, ultimately paving the way for an innovative approach to teaching aesthetics at the undergraduate level.